A suggested activity to develop integrated skills and a love of nature in children. (2nd April 2020) - Oztas Cin, Merve; Yurumezoglu, Kemal
Abstract: In this study, a process was designed, in which a lemon seed grew into a seedling, using the inquiry-based science learning approach. This aimed to increase the overall development of the scientific process skills of children and their sensitivity to nature. The germination, growth and development of a plant were meticulously and systematically observed in a long period from seed to seedling. This process contributed to the children's integration of scientific process skills based on observation and measurement and structuring of concepts related to germination, growth and development in science lessons. It also supported the development of children's love of nature through allowing them to make meaningful connections with nature.